Composite particle containing photocatalyst, preparation method of composite particle and water-based paint containing composite particle

By loading the photocatalyst nanoparticles on MXene nanosheets and combining them with silica aerogels to form three-dimensional aerogel particles, the problem of poor dispersion of nanoTiO2 powder in photocatalytic air purification latex paint is solved, and efficient and long-lasting formaldehyde purification effect is achieved, and production costs are reduced.

CN119708905APending Publication Date: 2025-03-28CHINA CONSTR EIGHT ENG DIV CORP LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411707888.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the existing photocatalytic air purification latex paint, the nano-TiO2 powder has poor dispersion, low formaldehyde removal efficiency, short duration, and high production cost.

Method used

MXene nanosheets supported with photocatalyst nanoparticles are combined with silica aerogel particles, and aerogel particles with three-dimensional structures are crosslinked by amino resin to form composite particles, and used in aqueous coatings.

Benefits of technology

The purification efficiency of formaldehyde (greater than 96%) and purification durability (greater than 86%) are improved, and water-based coatings have high environmental protection due to good dispersion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708905A_ABST
    Figure CN119708905A_ABST
Patent Text Reader

Abstract

The invention provides a composite particle containing a photocatalyst, which comprises aerogel particles and / or silicon dioxide aerogel particles, wherein the aerogel particles and / or the silicon dioxide aerogel particles are / is of a three-dimensional structure formed by crosslinking MXene nanosheets loaded with photocatalyst nanoparticles through amino resin shown in the formula (I), and in the # imgabs0 # formula, n is an integer of 1-50. The invention also provides a preparation method of the composite particle containing the photocatalyst. The invention also provides a water-based paint comprising the composite particle containing the photocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water-based coatings for photocatalytically degrading formaldehyde, and specifically relates to composite particles containing a photocatalyst and a preparation method thereof, and water-based coatings comprising the composite particles. Background Art

[0002] The formaldehyde in indoor air mainly comes from interior decoration and decoration materials, such as wood-based panels, paints, coatings, plywood, blockboard, medium-density fiberboard and particleboard. These materials usually use urea-formaldehyde resin as an adhesive during the production process, which may be the largest source of formaldehyde emissions. In addition, wallpaper, chemical fiber carpets, plastic floor tiles, foam plastics, etc. may also contain a certain amount of formaldehyde. Formaldehyde is a colorless, soluble, irritating gas that has a serious impact on human health. When the indoor content reaches a certain level, it will cause symptoms such as eye discomfort, sore throat, nausea and vomiting. Long-term exposure to low doses of formaldehyde may also cause chronic respiratory diseases, menstrual disorders, pregnancy syndrome, and even nasopharyngeal cancer.

[0003] The role and significance of air purification coatings are that they can reduce pollutants in indoor air, especially formaldehyde, through different mechanisms. These mechanisms include photocatalytic, physical adsorption, chemical reaction and composite. Photocatalytic air purification coatings rely on photocatalyst materials in the coating to decompose harmful substances such as formaldehyde into harmless substances under light conditions. Physical adsorption adsorbs pollutants in the air by adding porous substances with adsorption capacity, such as activated carbon, diatomaceous earth, etc. Chemical reaction coatings use active groups that can react chemically with formaldehyde to eliminate formaldehyde. Composite coatings combine two or more of the above mechanisms to achieve better purification effects. The significance of air purification coatings is that they can not only enhance the decorativeness of the indoor environment, but also effectively decompose harmful substances such as formaldehyde and benzene in the air, providing a safer and healthier indoor environment. These coatings are simple and convenient to use, meet the standard requirements of green buildings, and play an important role in improving the quality of living and working environments. With the improvement of people's awareness of health and environmental protection, the application of air purification coatings is becoming more and more extensive, and they play an increasingly important role in improving indoor air quality and protecting human health.

[0004] Chinese patent document CN101134858A discloses a photocatalytic air-purifying latex paint modified with metal-doped nano-TiO2 powder and a preparation method thereof, which is prepared from the following raw materials in percentage by mass: 2 to 5 parts of ethylene glycol, 0.5 to 1.5 parts of auxiliary agent A, 0.5 to 1.1 parts of auxiliary agent B, 0.1 to 0.3 parts of auxiliary agent C, 30 to 60 parts of pigments and fillers, 0.5 to 5.0 parts of metal-doped nano-TiO2 powder, 15 to 22 parts of emulsion, 15 to 22 parts of thickener aqueous solution, and 12 to 18 parts of water. Nano-TiO2 powder is used to prepare photocatalytic air-purifying latex paint. When TiO2 is irradiated with ultraviolet light, the electrons on its surface are excited and jump from the valence band to the conduction band to form photogenerated electrons and holes. Then, the photogenerated electrons and holes react with water molecules or oxygen adsorbed on the catalyst surface during migration to generate active species such as hydroxyl radicals or superoxide radicals with strong oxidizing properties. Finally, active species such as hydroxyl radicals or superoxide radicals undergo redox reactions with formaldehyde molecules in the air, gradually oxidizing and decomposing formaldehyde into carbon dioxide and water. After being doped with elements such as nitrogen, iron, and manganese, titanium dioxide has a narrower band gap, so that the electrons of TiO2 can be excited under visible light, thereby catalyzing the degradation of formaldehyde, thereby improving its utilization of natural light.

[0005] However, the research and application of air-purifying latex paints also face some challenges, such as poor dispersion of nano-TiO2 powder in latex paints, low formaldehyde removal efficiency and short duration, poor long-term stability and safety of the paint, and high production costs, etc. Summary of the invention

[0006] In view of the defects of the prior art, the purpose of the present invention is to provide a composite particle containing a photocatalyst and a preparation method thereof, and a water-based paint including the composite particle, so as to solve the problems of the existing formaldehyde-free latex paint, such as poor dispersibility of photocatalyst nano TiO2 powder in latex paint, low formaldehyde removal efficiency, and short duration.

[0007] To achieve the above purpose, the solution adopted by the present invention is as follows:

[0008] In a first aspect, the present invention provides a composite particle containing a photocatalyst, comprising a MXene nanosheet loaded with photocatalyst nanoparticles cross-linked with an amino resin represented by formula (I) to form a three-dimensional structure of aerogel particles and / or silica aerogel particles:

[0009]

[0010] Wherein, n is an integer of 1-50;

[0011] The MXene nanosheet is a two-dimensional layered titanium carbide nanosheet (Ti3C2T x), wherein T represents the terminal group of the layered surface, selected from one or more of -OH, -O and -F.

[0012] Preferably, the surface of the photocatalyst nanoparticles and / or the surface of the silica aerogel particles are modified by a surfactant.

[0013] Preferably, the surfactant is a silane coupling agent, preferably an aminosilane coupling agent, more preferably one or more of a monoaminosilane coupling agent, a bisaminosilane coupling agent and a triaminosilane coupling agent.

[0014] Preferably, the surfactant is one or more selected from 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane and γ-diethylenetriaminopropyltrimethoxysilane.

[0015] Preferably, the photocatalyst nanoparticles are doped titanium dioxide nanoparticles, and the doped titanium dioxide nanoparticles are selected from one or more of nitrogen-doped titanium dioxide nanoparticles, iron-doped titanium dioxide nanoparticles and manganese-doped titanium dioxide nanoparticles.

[0016] Preferably, the number average molecular weight of the amino resin represented by formula (I) is 230-2000 g / mol.

[0017] In a second aspect, the present invention further provides a method for preparing the composite particles containing the photocatalyst as described above, comprising the following steps:

[0018] Step (1), dissolving a surfactant and the amino resin represented by formula (I) as claimed in claim 1 in an organic solvent mixed with water to form a mixed solution;

[0019] Step (2), adding MXene nanosheet powder, silica aerogel powder and doped titanium dioxide nanopowder to the mixed solution of step (1), and stirring the mixture under heating reflux conditions to react;

[0020] Step (3), after the reaction is completed, the mixture is cooled, filtered and washed repeatedly with deionized water, and then freeze-dried and ground to obtain composite particles containing a photocatalyst.

[0021] Preferably, the weight parts of each raw material are: 3-5 weight parts of surfactant, 6-8 weight parts of amino resin, 4-6 weight parts of MXene nanosheet powder, 2-3 weight parts of silica aerogel powder, 12-15 weight parts of doped titanium dioxide nanopowder, and 100 weight parts of organic solvent mixed with water.

[0022] Preferably, the surfactant is a silane coupling agent, preferably an aminosilane coupling agent, more preferably one or more of a monoaminosilane coupling agent, a bisaminosilane coupling agent and a triaminosilane coupling agent, selected from 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane. one or more of; the organic solvent is selected from one or more of methanol, ethanol, n-propanol, isopropanol, acetone, methyl ethyl ketone and N-methyl-2-pyrrolidone; the number average molecular weight of the amino resin represented by formula (I) is 230-2000g / mol; the sheet diameter of the MXene nanosheet powder is 0.05-10μm; the particle size of the silica aerogel powder is 5-50μm; the doped titanium dioxide nanopowder is selected from one or more of nitrogen-doped titanium dioxide nanopowder, iron-doped titanium dioxide nanopowder and manganese-doped titanium dioxide nanopowder, and the particle size is 5-30nm.

[0023] Preferably, the mesh size of the composite particles containing the photocatalyst after grinding is 100-200 meshes.

[0024] Preferably, in step (2), the heating temperature is 65-75° C., the stirring speed is 400-600 rpm, the reaction time is 5-8 h, and the freeze-drying time is 12-24 h.

[0025] In a third aspect, the present invention further provides a water-based coating, comprising the composite particles containing a photocatalyst as described above and the composite particles containing a photocatalyst prepared by the preparation method as described above.

[0026] Preferably, the water-based paint comprises the following components in parts by weight: 45-55 parts by weight of acrylic emulsion, 5-8 parts by weight of composite particles containing photocatalyst, 15-25 parts by weight of pigments and fillers, 6-8 parts by weight of functional additives, 3-5 parts by weight of water-based color paste, and 10-15 parts by weight of deionized water.

[0027] Preferably, the acrylic emulsion is selected from one or more of pure acrylic emulsion, styrene acrylic emulsion, acetic acid acrylic emulsion, and silicone acrylic emulsion; the pigment filler is selected from one or more of titanium dioxide, talc and heavy calcium carbonate; the functional additive is selected from one or more of dispersant, defoamer, film-forming aid, pH regulator, thickener and preservative; the water-based color paste is selected from one or more of water-based organic color paste and water-based inorganic color paste.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The composite particles containing photocatalysts provided by the present invention and the preparation method thereof enhance the photocatalytic performance of the photocatalyst nanoparticles by means of MXene nanosheets loaded with photocatalyst nanoparticles, and enhance the adsorption of formaldehyde by means of silica aerogel particles, and have excellent formaldehyde purification efficiency (greater than 96%) and purification durability (R6 greater than 86%) under visible light; the water-based coating including the composite particles containing the photocatalysts has good dispersibility in the water-based coating, uses water as the medium, has a low organic solvent content, and is highly environmentally friendly. DETAILED DESCRIPTION

[0030] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and specific implementation methods.

[0031] <Composite particles containing photocatalyst>

[0032] The invention provides composite particles containing a photocatalyst, comprising aerogel particles having a three-dimensional structure formed by cross-linking MXene nanosheets loaded with photocatalyst nanoparticles through a curing agent.

[0033] In the composite particles containing photocatalysts of the present invention, the photocatalyst nanoparticles used in the present invention are visible light responsive titanium dioxide photocatalyst nanoparticles, which can be, for example, anatase titanium dioxide, rutile titanium dioxide, brookite titanium dioxide, etc., and can also be doped titanium dioxide nanoparticles doped with elements such as nitrogen, sulfur, carbon, fluorine, phosphorus, chromium, iron, cobalt, and manganese.

[0034] In the composite particles containing photocatalysts of the present invention, the MXene nanosheets used in the present invention are two-dimensional layered titanium carbide nanosheets (Ti3C2T x ), Al is removed from the MAX phase (Ti3AlC2) by etching and prepared by peeling, and the ends of the sheet surface have various groups such as -OH, -O or -F. In the composite particles containing photocatalysts of the present invention, the photocatalyst nanoparticles are loaded on MXene nanosheets.

[0035] In the composite particles containing a photocatalyst of the present invention, the curing agent used in the present invention is an amino resin represented by the following formula (I):

[0036]

[0037] In the formula, n is an integer of 1-50.

[0038] In the present invention, the above-mentioned resin with terminal primary amine groups and polyethylene glycol as the main chain is cured and cross-linked with MXene nanosheets loaded with photocatalyst nanoparticles, and the terminal primary amine groups on the amino resin are bridged with various groups such as -OH, -O or -F on the lamellae of the MXene nanosheets to form aerogel particles (or "sol particles") with a three-dimensional structure.

[0039] In the present invention, the amino resin represented by the above formula (I) can adopt amino resins with different number average molecular weights according to the length of the molecular chain, for example, Adamas D series polyetheramine products of Huntsman Company, such as D-230 (number average molecular weight of 230), D-400 (number average molecular weight of 400), D-2000 (number average molecular weight of 2000), etc.

[0040] In the composite particles containing photocatalysts of the present invention, the photocatalyst nanoparticles are loaded on MXene nanosheets. In order to enhance the binding force between the photocatalyst nanoparticles and the MXene nanosheets, the surface of the photocatalyst nanoparticles can also be modified by a surfactant. The surfactant used in the present invention is a silane coupling agent, preferably an aminosilane coupling agent, for example, a monoaminosilane coupling agent, a bisaminosilane coupling agent, a triaminosilane coupling agent, etc., for example, one or more aminosilane coupling agents of the following structural formula:

[0041] (1) 3-Aminopropylmethyldimethoxysilane:

[0042]

[0043] (2) 3-aminopropylmethyldiethoxysilane:

[0044]

[0045] (3) N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane:

[0046]

[0047] (4) N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane:

[0048]

[0049] (5) γ-aminopropyltrimethoxysilane:

[0050]

[0051] (6) γ-aminopropylmethyldiethoxysilane:

[0052]

[0053] (7) γ-aminopropyltriethoxysilane:

[0054]

[0055] (8) and γ-diethylenetriaminopropyltrimethoxysilane:

[0056]

[0057] In the composite particles containing photocatalysts of the present invention, as an optional scheme, silica aerogel particles (or "sol particles") can also be included. The silica aerogel particles used in the present invention have a particle size of 5-50 μm, have ultra-high porosity and specific surface area, and can improve the adsorption capacity of photocatalyst particles for formaldehyde.

[0058] In some embodiments, the silica aerogel particles may also be modified by the above-mentioned silane coupling agent to react with the hydroxyl groups on their surfaces to enhance their dispersibility in the aqueous emulsion.

[0059] <Preparation of Composite Particles Containing Photocatalyst>

[0060] The present invention also provides a method for preparing the composite particles containing the photocatalyst as described above, comprising the following steps:

[0061] Step (1), dissolving a surfactant and an amino resin represented by formula (I) in an organic solvent mixed with water to form a mixed solution;

[0062] Step (2), adding MXene nanosheet powder, silica aerogel powder and doped titanium dioxide nanopowder to the mixed solution of step (1), and stirring the mixture under heating reflux conditions to react;

[0063] Step (3), after the reaction is completed, the mixture is cooled, filtered and washed repeatedly with deionized water, and then freeze-dried and ground to obtain composite particles containing a photocatalyst.

[0064] In the above steps, the weight parts of each raw material are: 3-5 weight parts of surfactant, 6-8 weight parts of amino resin, 4-6 weight parts of MXene nanosheet powder, 2-3 weight parts of silica aerogel powder, 12-15 weight parts of doped titanium dioxide nanopowder, and 100 weight parts of organic solvent mixed with water.

[0065] In the above steps, the MXene nanosheet powder is Ti3C2T x , wherein T represents the terminal group on the surface of the sheet, including -OH, -O or -F, etc., the sheet diameter is 0.05-10μm, the particle size of the silica aerogel powder is 5-50μm, and the particle size of the doped titanium dioxide nanopowder is 5-30nm.

[0066] In the above steps, the heating reflux temperature is 65-75°C, the stirring speed is 400-600rpm, the reaction time is 5-8h, the freeze-drying time is 12-24h, and the mesh size of the composite particles containing the photocatalyst obtained after grinding is 100-200 mesh. The grinding method is, for example, the well-known ball milling, sand milling, etc. using dispersion media such as glass beads and zirconia beads.

[0067] In the preparation method of the composite particles containing the photocatalyst of the present invention, aminosilane coupling agent, polyetheramine, MXene nanosheet powder, silica aerogel powder and doped nano titanium dioxide powder are synthesized in an ethanol aqueous solution.

[0068] During the preparation process, the surfactant aminosilane coupling agent modifies the surface of the doped nano-titanium dioxide powder, so that when the doped nano-titanium dioxide powder is loaded on the MXene nanosheet layer structure, the doped nano-titanium dioxide powder and the MXene nanosheet have a strong binding force. At the same time, the surfactant aminosilane coupling agent can also modify the surface of the MXene nanosheet, enhance the affinity between the MXene nanosheet and the doped nano-titanium dioxide powder, and has excellent photothermal, ultraviolet light absorption and electronic conduction properties, which can enhance the photocatalytic degradation performance of doped titanium dioxide nanoparticles on formaldehyde.

[0069] During the preparation process, the amino resin adheres to the surface of the MXene nanosheets, promoting the dispersion of the MXene nanosheets in the aqueous solution. At the same time, it can also undergo a curing and cross-linking reaction at a heating reflux temperature of 65-75°C, cross-linking the MXene nanosheets loaded with doped titanium dioxide nanoparticles to form a three-dimensional aerogel structure of MXene nanosheets loaded with doped nano-titania after freeze-drying. This three-dimensional aerogel structure can not only avoid the agglomeration of MXene nanosheets loaded with doped nano-titania in water-based coatings and promote their dispersion, but also produce a larger specific surface area and more doped nano-titania and formaldehyde adsorption sites, thereby improving the photocatalytic activity of doped nano-titania.

[0070] Therefore, the composite particles containing photocatalysts prepared by the present invention, under the joint action of MXene nanosheets supported by doped nano-titanium dioxide and silica aerogel, have excellent formaldehyde adsorption and catalytic degradation effects, showing ultra-high formaldehyde purification efficiency and purification durability.

[0071] <Water-based paint>

[0072] The present invention also provides a water-based paint, comprising the composite particles containing the photocatalyst. The composite particles containing the photocatalyst prepared by the present invention have good dispersibility in the water-based paint.

[0073] The water-based coating of the present invention may also include the following conventional components:

[0074] (1) Thermosetting resins: such as epoxy resin, acrylic resin, polyurethane resin, silicone resin, etc.

[0075] (2) Inorganic pigments, organic pigments, dispersants, defoamers, film-forming aids, surfactants, pH adjusters, thickeners, preservatives, etc.;

[0076] (3) Water-based color paste.

[0077] The water-based coating of the present invention is applied on different substrates to form a coating. Different resin systems and additive components are selected according to different requirements.

[0078] In particular, in the present invention, a water-based paint containing composite particles of a photocatalyst is provided, which is applied on interior and exterior walls of buildings such as cement substrates, gypsum substrates, and ceramic substrates by roller coating or the like to form a coating film having excellent formaldehyde purification efficiency and purification durability under visible light and room temperature conditions.

[0079] As an example, the present invention further provides an air-purifying latex paint, comprising the following components in parts by weight: 45-55 parts by weight of acrylic emulsion, 5-8 parts by weight of composite particles containing photocatalysts, 15-25 parts by weight of pigments and fillers, 6-8 parts by weight of functional additives, 3-5 parts by weight of water-based color paste, and 10-15 parts by weight of deionized water.

[0080] In the components of the above-mentioned air purification latex paint, the acrylic emulsion is selected from one or more of pure acrylic emulsion, styrene acrylic emulsion, vinegar acrylic emulsion, and silicone acrylic emulsion; the pigment filler is selected from one or more of titanium dioxide, talcum powder and heavy calcium carbonate; the functional additive is selected from one or more of dispersant, defoamer, film-forming aid, pH adjuster, thickener and preservative; the water-based color paste is selected from one or more of water-based organic color paste and water-based inorganic color paste.

[0081] The present invention is further described below in conjunction with the embodiments, the purpose of which is to better understand the content of the present invention and embody the essential characteristics of the present invention, so the examples given should not be regarded as limiting the scope of protection of the present invention. Any product identical or similar to the present invention obtained by anyone under the enlightenment of the present invention or by combining the features of the present invention with other prior arts falls within the scope of protection of the present invention.

[0082] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0083] Embodiment 1:

[0084] In this example, composite particles A containing photocatalysts and water-based coatings A containing the composite particles are prepared by the following scheme:

[0085] S1. Dissolve the aminosilane coupling agent (3g, 3-aminopropylmethyldimethoxysilane APMDS) and amino resin (8g, Adamas D-400, average number average molecular weight ~400) in an ethanol aqueous solution (100g, volume fraction 75%), then add MXene nanosheet powder (5g, sheet diameter 2-10μm, Xianfeng Nano), silica aerogel powder (2g, 20 microns, Suzhou Kangmai New Materials), doped nano-titanium dioxide powder (12g, nitrogen-doped nano-titanium dioxide, 10nm, Zhiti Nano), and stir the reaction under heating reflux conditions (heating temperature 75°C, stirring speed 500rpm, reaction time 8h). After the reaction is completed, let it stand and cool, repeatedly filter and wash with deionized water, and finally freeze-dry (freeze-drying time 24h) and dry grind (150 mesh sieving) to obtain composite particles A containing photocatalyst.

[0086] S2. Acrylic emulsion (48 g, pure acrylic emulsion, Badford RS-2788), composite particles A containing photocatalyst (6 g), pigments and fillers (6 g titanium dioxide (Longmang R-996), 8 g talc (Xibian 3000 mesh), 6 g heavy calcium carbonate (Shengshe 3000 mesh)), functional additives (dispersant (1 g, BASF DISPEX ULTRA FA 4425AN), defoamer (2 g, TegoFoamex 810), film-forming aid (2 g, alcohol ester twelve, Eastman), pH adjuster (1 g, Solvay DMEA), thickener (1 g, Haimingsi RHEOLATE 299)), water-based color paste (4 g, yellow, diaryl yellow, BASF Dispers Yellow 1780) and deionized water (15 g) are mixed and stirred (stirring speed 1200 rpm, stirring time 60 min) to obtain water-based coating A.

[0087] Embodiment 2:

[0088] In this example, composite particles B containing photocatalysts and water-based coatings B of the composite particles are prepared by the following scheme:

[0089] S1. Dissolve the aminosilane coupling agent (5g, 3-aminopropylmethyldiethoxysilane) and amino resin (6g, Adamas D-230, average number average molecular weight ~230) in a methanol aqueous solution (100g, volume fraction 50%), then add MXene nanosheet powder (4g, sheet diameter 2-5μm, Xianfeng Nano)), silica aerogel powder (3g, 15 microns, Shenzhen Zhongning Technology), doped nano-titanium dioxide powder (15g, iron-doped nano-titanium dioxide, 5nm, Zhiti Nano), and stir the reaction under heating reflux conditions (heating temperature 65°C, stirring speed 600rpm, reaction time 5h). After the reaction is completed, let it stand and cool, repeatedly filter and wash with deionized water, and finally freeze-dry (freeze-drying time 12h) and dry grind (100 mesh sieving) to obtain composite particles B containing photocatalyst.

[0090] S2. Acrylic emulsion (55 g, styrene-acrylic emulsion, Badford RS-998A), composite particles B containing photocatalyst (5 g), pigments and fillers (4 g titanium dioxide (Longmang R-996), 6 g talc (Xibian 3000 mesh), 5 g heavy calcium carbonate (Shengshe 3000 mesh)), functional additives (dispersant (1 g, BASF Disponil A 1080), defoamer (2 g, BASF FoamStar SI2210), film-forming aid (2 g, dipropylene glycol methyl ether, Dow), pH adjuster (0.5 g, Solvay DMEA), thickener (0.5 g, BASF Rheovis HS1130)), water-based color paste (5 g, yellow, transparent iron oxide hydrate, BASF Luconyl Yellow 1995) and deionized water (14 g) are mixed and stirred (stirring speed 1500 rpm, stirring time 120 min) to obtain water-based coating B.

[0091] Embodiment 3:

[0092] In this example, composite particles C containing photocatalysts and water-based coatings C containing the composite particles are prepared by the following scheme:

[0093] S1. Dissolve an aminosilane coupling agent (4 g, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane) and an amino resin (7 g, Adamas D-2000, average number average molecular weight ~2000) in an aqueous solution of n-propanol (100 g, volume fraction 75%), then add MXene nanosheet powder (6 g, sheet diameter 0.5-3 μm, Xianfeng Nano)), silica aerogel powder (2.5 g, 50 microns, Shenzhen Zhongning Technology), doped nano-titanium dioxide powder (13 g, manganese-doped nano-titanium dioxide, 10 nm, Zhiti Nano), and stir the reaction under heating reflux conditions (heating temperature 75°C, stirring speed 400 rpm, reaction time 6 h). After the reaction is completed, let it stand and cool, repeatedly filter and wash with deionized water, and finally freeze-dry (freeze-drying time 18 h) and dry grind (200 mesh sieving) to obtain composite particles C containing photocatalyst.

[0094] S2. Acrylic emulsion (45g, acetic acid acrylic emulsion, Baolijia Chemical BLJ-3359), composite particles C containing photocatalyst (8g), pigments and fillers (8g titanium dioxide (Longmang R-996), 9g talc (Xibian 3000 mesh), 8g heavy calcium carbonate (Shengshe 3000 mesh)), functional additives (dispersant (2g, Arkema COADIS 615), defoamer (2g, Solvay DF691), film-forming aid (2g, dipropylene glycol butyl ether, Dow), pH adjuster (1g, Solvay DMEA), thickener (1g, Carbomer Carbomer941)), water-based color paste (3g, green, water-based phthalocyanine green paste, BASF Dispers Green 8730) and deionized water (11g) are mixed and stirred (stirring speed 1000rpm, stirring time 90min) to obtain water-based coating C.

[0095] Embodiment 4:

[0096] In this example, composite particles D containing photocatalysts and water-based coatings D containing the composite particles are prepared by the following scheme:

[0097] S1. Dissolve the aminosilane coupling agent (3.5 g, γ-diethylenetriaminopropyltrimethoxysilane) and amino resin (7.5 g, Adamas D-400, average number average molecular weight ~400) in an isopropanol aqueous solution (100 g, volume fraction 60%), then add MXene nanosheet powder (5.5 g, sheet diameter 0.05-1 μm, Xianfeng Nano)), silica aerogel powder (3 g, 5 microns, Suzhou Kangmai New Materials), doped nano-titanium dioxide powder (14 g, nitrogen-doped nano-titanium dioxide, 5 nm, Zhiti Nano), and stir the reaction under heating reflux conditions (heating temperature 75°C, stirring speed 600 rpm, reaction time 7 h). After the reaction is completed, let it stand and cool, repeatedly filter and wash with deionized water, and finally freeze-dry (freeze-drying time 15 h) and dry grind (150 mesh sieving) to obtain composite particles D containing photocatalyst.

[0098] S2. Acrylic emulsion (50 g, silicone-acrylic emulsion, Badfu RS996AD), ​​composite particles D containing photocatalyst (7 g), pigments and fillers (5 g titanium dioxide (Longmang R-996), 7 g talc (Xibian 3000 mesh), 6 g heavy calcium carbonate (Shengshe 3000 mesh)), functional additives (dispersant (2.5 g, Zhongya PE-100), defoamer (1.5 g, Gas Chemical Surfynol 104E), film-forming aid (2 g, alcohol ester twelve, Eastman), pH adjuster (0.5 g, Solvay DMEA), thickener (0.5 g, Sannopco 612NC)), water-based color paste (5 g, white, water-based titanium dioxide paste, BASF Dispers White 0022) and deionized water (13 g) are mixed and stirred (stirring speed 1300 rpm, stirring time 100 min) to obtain water-based coating D.

[0099] Embodiment 5:

[0100] In this example, composite particles E containing photocatalysts and water-based coating E of the composite particles are prepared by the following scheme:

[0101] S1. Dissolve the aminosilane coupling agent (5g, γ-aminopropyltriethoxysilane KH-550) and amino resin (6g, Adamas D-230, average number average molecular weight ~230) in ethanol aqueous solution (100g, volume fraction 70%), then add MXene nanosheet powder (6g, sheet diameter 1-5μm, Xianfeng Nano)), silica aerogel powder (2.6g, 30 microns, Suzhou Kangmai New Materials), doped nano-titanium dioxide powder (12g, iron-doped nano-titanium dioxide, 10nm, Zhiti Nano), and stir the reaction under heating reflux conditions (heating temperature 70°C, stirring speed 500rpm, reaction time 8h). After the reaction is completed, let it stand and cool, repeatedly filter and wash with deionized water, and finally freeze-dry (freeze-drying time 20h) and dry grind (150 mesh sieving) to obtain composite particles E containing photocatalyst.

[0102] S2. Acrylic emulsion (52 g, pure acrylic emulsion, Badford RS-2788), composite particles E containing photocatalyst (5 g), pigments and fillers (7 g titanium dioxide (Longmang R-996), 7 g talc (Xibian 3000 mesh), 8 g heavy calcium carbonate (Shengshe 3000 mesh)), functional additives (dispersant (3 g, Ningbadi FLUIJET 1725), defoamer (2 g, San Nopco SN-1311), film-forming aid (2 g, alcohol ester twelve, Eastman), pH adjuster (0.5 g, Solvay DMEA), thickener (0.5 g, Nobel ALCOGUM L344)), water-based color paste (3 g, black, water-based carbon black paste, BASF Dispers Black 0066) and deionized water (10 g) are mixed and stirred (stirring speed 1300 rpm, stirring time 100 min) to obtain water-based coating E.

[0103] Comparative Example 1:

[0104] Based on Example 1, no MXene nanosheets and amino resin were added.

[0105] Comparative Example 2:

[0106] On the basis of Example 1, no silica aerogel powder was added.

[0107] Comparative Example 3:

[0108] On the basis of Example 1, no doped nano titanium dioxide powder is added.

[0109] Comparative Example 4:

[0110] Based on Example 1, no aminosilane coupling agent was added.

[0111] Comparative Example 5:

[0112] Based on Example 1, no polyetheramine was added.

[0113] Comparative Example 6: (Bamboo charcoal powder formaldehyde-free latex paint)

[0114] This comparative example prepares bamboo charcoal powder air purification latex paint by the following scheme

[0115] Acrylic emulsion (48g, pure acrylic emulsion, Badfu RS-2788), bamboo charcoal powder (6g, 1000 mesh), pigments and fillers (6g titanium dioxide (Longmang R-996), 8g talc (Xibian 3000 mesh), 6g heavy calcium carbonate (Shengshe 3000 mesh)), functional additives (dispersant (1g, BASF DISPEX ULTRA FA 4425AN), defoamer (2g, Tego Foamex 810), film-forming aid (2g, alcohol ester twelve, Eastman), pH adjuster (1g, Solvay DMEA), thickener (1g, Haimingsi RHEOLATE299)), water-based color paste (4g, yellow, diaryl yellow, BASF Dispers Yellow 1780) and deionized water (15g) are mixed and stirred (stirring speed 1200rpm, stirring time 60min) to obtain bamboo charcoal powder air purification latex paint.

[0116] Comparative Example 7:

[0117] Based on Comparative Example 6, no bamboo charcoal powder was added.

[0118] In the above specific example, the prepared air-purifying latex paint is prepared for test samples according to the water-based liquid coating material (Class 1S) in the standard "JC / T 1074-2021 Purification Performance of Indoor Air Purification Functional Coating Materials", and formaldehyde is selected as the target pollutant. The purification principle is based on the photocatalytic air purification function coating material (Type G, visible light source) for performance testing.

[0119] The test results of the corresponding properties of the products formed by Examples 1 to 5 and the products formed by Comparative Examples 1 to 7 are shown in Table 1 below.

[0120] Table 1

[0121]

[0122]

[0123] It can be seen from the test results of Table 1 that the air purification latex paint prepared by the present invention has excellent formaldehyde purification efficiency and purification durability under visible light and room temperature conditions compared to air purification latex paint without MXene nanosheets, air purification latex paint without aerogel, air purification latex paint without doping nano titanium dioxide, bamboo charcoal powder air purification latex paint, and latex paint without adding purification materials, indicating that in the air purification latex paint of the present invention, MXene nanosheets, silica aerogels, and doped nano titanium dioxide have a mutual synergistic effect on formaldehyde purification efficiency and purification durability. In the air purification latex paint prepared by Comparative Example 4 without aminosilane coupling agent, the dispersibility of MXene nanosheets, silica aerogels, and doped nano titanium dioxide in latex paint is all deteriorated, and a uniform emulsion cannot be formed. In the air purification latex paint prepared by Comparative Example 5 without amino resin, MXene nanosheets cannot form a three-dimensional aerogel structure, and compared with Example 1, formaldehyde purification efficiency and purification durability are also greatly reduced. Moreover, the storage stability of the air purification latex paint prepared by Comparative Example 4 without an aminosilane coupling agent and Comparative Example 5 without an amino resin is not as good as that of Example 1.

[0124] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A composite particle containing a photocatalyst, characterized in that: The invention comprises MXene nanosheets loaded with photocatalyst nanoparticles and cross-linked with an amino resin represented by formula (I) to form a three-dimensional structure of aerogel particles and / or silica aerogel particles: Wherein, n is an integer of 1-50; in, The MXene nanosheet is a two-dimensional layered titanium carbide nanosheet (Ti3C2T x ), wherein T represents the terminal group of the lamellar surface, selected from one or more of -OH, -O and -F; The surfaces of the photocatalyst nanoparticles and / or the surfaces of the silica aerogel particles are modified by a surfactant.

2. The composite particle containing a photocatalyst according to claim 1, characterized in that The surfactant is a silane coupling agent, preferably an aminosilane coupling agent, more preferably one or more of a monoaminosilane coupling agent, a bisaminosilane coupling agent and a triaminosilane coupling agent; further preferably, the surfactant is selected from one or more of 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane and γ-diethylenetriaminopropyltrimethoxysilane.

3. The composite particle containing a photocatalyst according to claim 1, characterized in that The photocatalyst nanoparticles are doped titanium dioxide nanoparticles, and the doped titanium dioxide nanoparticles are selected from one or more of nitrogen-doped titanium dioxide nanoparticles, iron-doped titanium dioxide nanoparticles and manganese-doped titanium dioxide nanoparticles.

4. The composite particle containing a photocatalyst according to claim 1, characterized in that The number average molecular weight of the amino resin represented by formula (I) is 230-2000 g / mol.

5. A method for preparing composite particles containing a photocatalyst according to any one of claims 1 to 4, characterized in that: The steps include: Step (1), dissolving a surfactant and the amino resin represented by formula (I) as claimed in claim 1 in an organic solvent mixed with water to form a mixed solution; Step (2), adding MXene nanosheet powder, silica aerogel powder and doped titanium dioxide nanopowder to the mixed solution of step (1), and stirring the mixture under heating reflux conditions to react; Step (3), after the reaction is completed, the mixture is cooled, filtered and washed repeatedly with deionized water, and then freeze-dried and ground to obtain composite particles containing a photocatalyst.

6. The preparation method according to claim 5, characterized in that: The weight proportions of the raw materials are: 3-5 weight proportions of surfactant, 6-8 weight proportions of amino resin, 4-6 weight proportions of MXene nanosheet powder, 2-3 weight proportions of silica aerogel powder, 12-15 weight proportions of doped titanium dioxide nanopowder, and 100 weight proportions of organic solvent mixed with water.

7. The preparation method according to claim 5, characterized in that: The surfactant is a silane coupling agent, preferably an aminosilane coupling agent, more preferably one or more of a monoaminosilane coupling agent, a bisaminosilane coupling agent and a triaminosilane coupling agent, selected from 3-aminopropylmethyldimethoxysilane, 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane; the organic solvent is selected from one or more of One or more of alcohol, ethanol, n-propanol, isopropanol, acetone, methyl ethyl ketone and N-methyl-2-pyrrolidone; the number average molecular weight of the amino resin represented by formula (I) is 230-2000g / mol; the sheet diameter of the MXene nanosheet powder is 0.05-10μm; the particle size of the silica aerogel powder is 5-50μm; the doped titanium dioxide nanopowder is selected from one or more of nitrogen-doped titanium dioxide nanopowder, iron-doped titanium dioxide nanopowder and manganese-doped titanium dioxide nanopowder, and the particle size is 5-30nm; the mesh number of the composite particles containing the photocatalyst after grinding is 100-200 mesh.

8. The preparation method according to claim 5, characterized in that: In step (2), the heating temperature is 65-75° C., the stirring speed is 400-600 rpm, the reaction time is 5-8 h, and the freeze-drying time is 12-24 h.

9. A water-based paint, characterized in that: The invention comprises composite particles containing a photocatalyst as described in any one of claims 1 to 4 and composite particles containing a photocatalyst prepared by the preparation method as described in any one of claims 5 to 8.

10. The water-based paint according to claim 9, characterized in that: The water-based paint comprises the following components in parts by weight: 45-55 parts by weight of acrylic emulsion, 5-8 parts by weight of composite particles containing photocatalysts, 15-25 parts by weight of pigments and fillers, 6-8 parts by weight of functional additives, 3-5 parts by weight of water-based color paste, and 10-15 parts by weight of deionized water; wherein the acrylic emulsion is selected from one or more of pure acrylic emulsion, styrene acrylic emulsion, acetic acid acrylic emulsion, and silicone acrylic emulsion; the pigments and fillers are selected from one or more of titanium dioxide, talc, and heavy calcium carbonate; the functional additives are selected from one or more of dispersants, defoamers, film-forming additives, pH regulators, thickeners, and preservatives; and the water-based color paste is selected from one or more of water-based organic color pastes and water-based inorganic color pastes.

Citation Information

Patent Citations

  • Metal doping nano TiO2 powder modified photocatalysis air purification emulsion paint and method for making same

    CN101134858A